Sintilimab treatment for chronic active Epstein–Barr virus infection and Epstein–Barr virus-associated hemophagocytic lymphohistiocytosis in children - Ruyue Chen; Qiang Lin; Yun Zhu; Yunyan Shen; Qinying Xu; Hanyun Tang; Ningxun Cui; Lu Jiang; Xiaomei Dai; Weiqing Chen; Xiaozhong Li (Orphanet Journal of Rare Diseases, 2023)
Abstract Background Chronic active Epstein–Barr virus infection (CAEBV) and Epstein–Barr virus-associated hemophagocytic lymphohistiocytosis (EBV-HLH) are rare but life-threatening progressive diseases triggered by EBV infection. Glucocorticoid/immunosuppressants treatment is temporarily effective; however, most patients relapse and/or progress. Hematopoietic stem cell transplantation (HSCT) is a potentially curative therapy; however, there are risks of transplantation-associated complications. Currently there is no standard treatment for CAEBV and EBV-HLH. Programmed death protein 1 (PD-1) inhibitors have achieved a high response in many EBV-related diseases. Sintilimab (a recombinant human IgG4 monoclonal antibody against PD-1) disrupts the interaction between PD-1 and its ligand, leading to T cell reinvigoration. Methods A retrospective analysis was performed on three children with CAEBV or EBV-HLH in the Children’s Hospital of Soochow University between 12 December 2020 and 28 November 2022. The efficacy of sintilimab was evaluated. Results Three patients, including two males and one female, were analyzed. Among them, two children were diagnosed with CAEBV with intermittent fever for more than four years, and one child was diagnosed with EBV-HLH. After sintilimab treatment and a mean follow-up of 17.1 months (range 10.0–23.3 months), patients 1 and 3 achieved a complete clinical response and patient 2 achieved a partial clinical response. All three children showed a > 50% decrease in EBV-DNA load in both blood and plasma. EBV-DNA copies in sorted T, B, and NK cells were also markedly decreased after sintilimab treatment. Conclusion Our data supported the efficacy of PD-1 targeted therapy in certain patients with CAEBV and EBV-HLH, and suggested that sintilimab could provide a cure for these diseases, without HSCT. More prospective studies and longer follow-up are needed to confirm these conclusions.